2022
DOI: 10.1111/asj.13790
|View full text |Cite
|
Sign up to set email alerts
|

Effects of compound of hawthorn (Crataegus pinnatifida) and Chinese yam (Dioscorea opposita Thunb.) extracts on growth performance, intestinal health, and immune function in weaned pigs

Abstract: Plant extracts were considered as natural resources to alleviate weaning stress in pig production. A 28‐day study (Phase 1: d 0–14 and Phase 2: d 15–28) was conducted to investigate the effects of compound of hawthorn and yam extracts on growth performance, intestinal health, and immune function in weaned pigs. A total of 144 weaned pigs with average body weight (BW) of 7.89 ± 1.09 kg were assigned to three treatments with six replicates pens by BW and sex. Dietary treatments included negative control (NC), co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Researchers found that dietary supplementation with the hawthorn pulp improved intestinal morphology by increasing villi length, villi width, and muscle thickness, and enhanced gut barrier integrity by increasing the mRNA expression of zonula occludens‐3 in golden pompano (Tan et al., 2020). It also improved intestinal health by improving duodenal lipase and trypsin activity and jejunal morphology, as well as higher ileal valproic acid, colonic propionic acid, and isobutyric acid concentrations (Fu et al., 2022). In addition, hawthorn extract can promote gastrointestinal motility by increasing the number of gastrointestinal Cajal (interstitial cell of Cajal [ICC]) mesenchymal cells through upregulation of c‐kit expression (Wang, Luo et al., 2021).…”
Section: Bioactivities Based On In Vitro and In Vivo Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers found that dietary supplementation with the hawthorn pulp improved intestinal morphology by increasing villi length, villi width, and muscle thickness, and enhanced gut barrier integrity by increasing the mRNA expression of zonula occludens‐3 in golden pompano (Tan et al., 2020). It also improved intestinal health by improving duodenal lipase and trypsin activity and jejunal morphology, as well as higher ileal valproic acid, colonic propionic acid, and isobutyric acid concentrations (Fu et al., 2022). In addition, hawthorn extract can promote gastrointestinal motility by increasing the number of gastrointestinal Cajal (interstitial cell of Cajal [ICC]) mesenchymal cells through upregulation of c‐kit expression (Wang, Luo et al., 2021).…”
Section: Bioactivities Based On In Vitro and In Vivo Studiesmentioning
confidence: 99%
“…The whole hawthorn fruit and its components also had other in vivo beneficial functions. The whole hawthorn extract could also enhance immune response and growth performance (Fu et al., 2022). Hawthorn pulp was sufficient to produce anxiolytic and antidepressant‐like effects by activating 5‐HT1A receptors and elevating brain‐derived neurotrophic factor, increasing urinary serotonin levels, and decreasing urinary NE and DA levels (Nitzan et al., 2022).…”
Section: Bioactivities Based On In Vitro and In Vivo Studiesmentioning
confidence: 99%
“…Emerging evidence have showed that plants and their extracts exert positive roles in animal growth, immunity, and maintaining animal health ( 1 ). The yucca extract contains saponins, polysaccharides, polyphenols, and other active substances ( 2 ), and is generally recognized as a safe feed additive.…”
Section: Introductionmentioning
confidence: 99%
“…(4,5) Alternatives to reduce the use of GPA in animals while maintaining efficient production and obtaining high-quality, low-cost foods are being sought. (2,6) Humic substances (HS) are potential alternatives as growth promoters as they have been shown to improve production efficiency and health in animals. (7,8,9) The most concentrated commercial sources of HS are leonardite and lignite, which are obtained from mines, and are extensively used to improve crop yields in agriculture; to a lesser extent, they are used as growth promoters in animals.…”
Section: Introductionmentioning
confidence: 99%